Paul Powell of Illinois : a lifelong Democrat - Hartley, Robert E. (Southern Illinois University Press, 1999)
Paul Powell emerged from the hill country of southern Illinois to serve in state government from 1935 until his death in 1970. His political tenure included three terms as Speaker of the Illinois House, four terms as minority leader, and two terms as secretary of state. The sponsor of hundreds of bills, he worked tirelessly for his constituents in southern Illinois. He also worked tirelessly to promote his own interests. In this first political biography of Powell, Robert E. Hartley follows the money. He tells how this man of humble origins and meager means amassed a world-class political and financial base. Part of that story is the disclosure of a personal fortune that boggled minds, including the unbelievable yarn of the 8 00,000 cash found in the hotel room following Powell's death. Powell never earned a state salary of more than 30,000 per year, yet in the last year of his life, his federal income tax return showed an income of more than 2 00,000. At his death his estate totaled 3 .2 million, and, when settled in 1978, was worth 4 .6 million, including nearly 1 million in racetrack stock. Following Powell's story, Hartley takes us deep into the Illinois political world of the 1940s, 1950s, and 1960s, a time when politicians were on an honor system regarding their financial holdings. This was before disclosure of political contributions, before computer records, and before public meetings laws. -- Provided by publisher.